PIC projects and applications using C : a project-based approach - Smith, David W., 1949- (Newnes, 2013)
This applications book details how to program the PIC Microcontroller in the C language. The book takes a learn-by- doing approach, with applications covering topics such as inputs, outputs, keypads, alpha numeric displays, analogue to digital conversion, radio transmitters and receivers, Data EEPROM, Interrupts and timing. To aid the debugging of the system there is a section detailing the use of the simulator and In Circuit Debugger. With this book you will learn: How to program the PIC microcontroller in C. Techniques for using the simulator and debuggers to find faults on your code. The ins and outs of interfacing circuits such as radio modules and liquid crystal displays. How to use the PIC on board functions such as interrupts and timing modules and make analogue measurements. Relevant parts of the language are introduced and explained as and when required for those new to the subjectCore principles are introduced gradually, enabling you to develop your understanding at your own paceExplains how and why a software program works, and how to alter and expand the code.